Arctic metrology: calibration of radiosondes ground check sensors in Ny‐Ålesund. (6th July 2015) - Musacchio, Chiara; Bellagarda, Simone; Maturilli, Marion; Graeser, Jürgen; Vitale, Vito; Merlone, Andrea
ABSTRACT: The Arctic research village of Ny‐Ålesund (79 ° N, 12 ° E) on the Spitsbergen island of Svalbard archipelago, with its logistics and infrastructure, provides a unique access to the Arctic environment. Among the several international environmental and climate monitoring programmes constantly running there, the Global Climate Observing System (GCOS) Reference Upper Air Network (GRUAN) has established one of its stations at the Alfred Wegener Institute observatory. Calibration of sensors and measurement traceability are fundamental aspects of climate observations, as requested by the GRUAN measurement procedures. In the framework of the MeteoMet project, a transportable climatic chamber for the calibrations of air temperature and pressure sensors was studied and manufactured. In June 2014, a calibration campaign involved the transport and use of one of those systems in the Ny‐Ålesund GRUAN station. The result of the campaign has been the complete calibration of temperature and pressure sensors for radiosonde pre‐launch ground checks. The resulting calibration curves were obtained with lower uncertainties and more robust characterization of the sensors, with respect to the usual procedures adopted. Given the opportunity of the calibration device operating already in place and the presence of the metrology staff, the calibration was extended to the sensors equipping the Amundsen‐Nobile Climate Change Tower. The present study reports on the 'Arctic metrology 2014' campaign and the plans for the establishment of a permanent laboratory for metrology in Ny‐Ålesund. The aim is to address the measurement traceability needs arising from the multidisciplinary measurements made by the scientific community operating there.